2010 6th International Symposium on Turbo Codes &Amp; Iterative Information Processing 2010
DOI: 10.1109/istc.2010.5613805
|View full text |Cite
|
Sign up to set email alerts
|

Universal LDPC codes for cooperative communications

Abstract: Cooperative communication is a well known technique to yield transmit diversity in the case of fading channels and to increase the spectral efficiency in the case of Gaussian channels. Error-correcting codes have to be carefully designed to achieve the promised gains. Good LDPC codes are known for fading channels and for Gaussian channels, but an LDPC code ensemble that performs well on both channels has not yet been presented in the literature. This paper merges two families of LDPC codes into a universal LDP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…This does not directly serve the performance analysis for the BF channel. However, an analysis in the real space of the fading coefficients has shown that this can be used to increase the coding gain on a BF relay channel [12]. But the optimization of the coding gain is outside the scope of this paper and here we will only use Proposition 5 in the application of Eq.…”
Section: B)mentioning
confidence: 99%
See 1 more Smart Citation
“…This does not directly serve the performance analysis for the BF channel. However, an analysis in the real space of the fading coefficients has shown that this can be used to increase the coding gain on a BF relay channel [12]. But the optimization of the coding gain is outside the scope of this paper and here we will only use Proposition 5 in the application of Eq.…”
Section: B)mentioning
confidence: 99%
“…In more recent work [12] we optimized the degree distribution using the analysis of Section V. Another method is based on density evolution with a modified Gaussian approximation that takes into account the SNR variation in one received codeword as well as the rate-compatibility constraint [28].…”
Section: A Density Evolution Outagementioning
confidence: 99%